Inventory and identification dragonfly Family Libellulidae at Slamet Reservoir, Surabaya, East Java - Muhamad Azmi Dwi Susanto (Journal on Biology and Instruction, 2021)
Slamet Reservoir is an artificial reservoir located in the lowlands of urban areas. The existence of this reservoir with a stagnant water habitat type has great potential to become a natural habitat for various types of dragonflies, especially the Libellulidae family. This study aims to inventory and identify the types of dragonflies in the family Libellulidae in the Slamet Reservoir. In this study, the Visual Encounter Survey (VES) method was modified by using the Belt Transect method. This method is an observation by following a predetermined circular line. Sampling was carried out by catching adult dragonflies using insect nets and then preserving them using 50% acetone. After preservation, the body part of the dragonfly was measured using a caliper. The results showed that in the Slamet Reservoir there were 12 species of dragonflies from the Libellulidae family with a total of 131 individuals. The species with the highest relative abundance value in the Slamet reservoir is Brachythemis contaminata with a value of 51.15%. While the species with the lowest relative abundance values were Acisoma panorpoides, Diplacodes trivialis and Pantala flavescens with a value of 0.76%.